A novel, fixed‐dose calcipotriol and betamethasone dipropionate cream for the topical treatment of plaque psoriasis: Direct and indirect evidence from phase 3 trials discussed at the 30th EADV Congress 2021. (22nd December 2022) - Pinter, Andreas; Gold, Linda Stein; Reich, Adam; Green, Lawrence J.; Praestegaard, Morten; Selmer, Johan; Armstrong, April W.; Danø, Anne; Dhawan, Sunil; Galván, Jordi; Stallknecht, Sandra E.; Trebbien, Paw; et al.
Abstract: Four posters about the novel, fixed‐dose calcipotriol and betamethasone dipropionate cream (CAL/BDP cream) based on Poly‐Aphron Dispersion (PAD) Technology were presented at the 30 th European Academy of Dermatology and Venereology (EADV) Congress 2021 and are summarized here. CAL/BDP cream was compared in two randomized, phase 3 trials to vehicle and active comparator (CAL/BDP gel/topical suspension [TS]) in adults with plaque psoriasis (NCT03802344 and NCT03308799). Pooled data from both trials demonstrated significant greater efficacy in favour of CAL/BDP cream for all efficacy endpoints, including PGA treatment success, mPASI, and mPASI75 compared to CAL/BDP gel/TS. CAL/BDP cream was well tolerated and comparable to CAL/BDP gel/TS with no adverse drug reactions with a frequency >1%. In the NCT03308799 study, CAL/BDP cream demonstrated a substantial improvement in the proportion of participants achieving a minimum 4‐point improvement on the peak pruritus numeric rating scale (NRS) score compared with vehicle at Weeks 1, 4 and 8. CAL/BDP cream also improved quality of life (QoL), as assessed through the Dermatology Life Quality Index (DLQI), and the EQ‐VAS at Week 8 compared with active comparator. Treatment convenience of CAL/BDP cream, as measured by the Psoriasis Treatment Convenience Scale, was superior to CAL/BDP gel/TS at all studied timepoints, including questions addressing formulation's greasiness and overall treatment satisfaction. Finally, an indirect comparison following the Bucher's method of adjusted indirect comparison and the difference‐in‐differences method was conducted to compare CAL/BDP cream and CAL/BDP foam, as both therapies have been compared to CAL/BDP gel/TS. Indirect evidence showed that treatment with CAL/BDP cream was associated with a trend for greater QoL improvement than CAL/BDP foam when DLQI improvement was assessed at the recommended treatment duration of 8 weeks for CAL/BDP cream and 4 weeks for CAL/BDP foam. CAL/BDP cream was statistically superior versus CAL/BDP foam in four out of five treatment satisfaction domains.